Effects of applying different organic and inorganic soil amendments to improve the late stage of reclaimed soil from abandoned homesteads on soil nutrients and maize yield - Ruiqing Zhang; Ruiqing Zhang; Ruiqing Zhang; Tingting Meng; Tingting Meng; Tingting Meng; Zenghui Sun; Zenghui Sun; Zenghui Sun; Zhe Liu; Zhe Liu; Zhe Liu (Frontiers in Sustainable Food Systems)
Abandoned homesteads in hollow villages are important reclamation resources, and how to improve the fertility of reclaimed soil is an important issue. In this paper, the effect of maturing agent (ferrous sulfate), organic fertilizer (well-composted chicken manure) and fly ash on the post-amelioration of soil maturation of the abandoned homesteads was investigated in different ratios using a field plot experiment by stripping topsoil, backfilling homesteads soil and adding clinker materials. The results of the study showed that the maturing agent + organic fertilizer (T1), fly ash + organic fertilizer (T2) and organic fertilizer (T3) treatments had a better effect on the improvement of organic matter, total nitrogen, total phosphorus, available phosphorus and available potassium of the reclaimed soil and were significantly higher than that of the inorganic treatments; and that the increase in soil nutrients showed a trend of increasing and then decreasing as the year lengthened in the period of 2019–2021. After 5 years of improvement, soil nutrient content increased from low level 5 to intermediate level 3. Maize yield under each treatment was also higher at T1, T2 and T3; comparing the time span, maize yield was highest in 2010 with an average of 7,724 kg/hm2; significantly higher than in 2019 and 2021. Correlation heat map analysis showed that maize yield had negative highly significant correlation with soil bulk density and positive highly significant correlation with soil organic matter. Based on the results of this study, it is recommended that at the later stage of raw soil maturation and soil improvement, it can be considered to reduce the addition of inorganic amendments and focus on increasing the organic and inorganic matter rationing, which can provide technical support for the rapid improvement of nutrients in reclaimed arable land.